Study on Forecasting Model of Maximum Daily Power Load in Beijing Area - Yuheng SHI; Na ZHAO; Ling WANG; Lijia XU; Jie ZHOU; Qian LIN; Yuan QIAO (Zhongguo dianli)
The characteristics of maximum daily power load and the dependence of maximum daily power load on meteorological factors are analyzed in this paper based on the records of the power load and auto weather station meteorological data of Beijing from 2009 to 2013. A maximum daily power load forecasting model is established through multivariable linear regression. The results of the study indicate that the maximum daily power load occurs between 9 BST and 17BST, obviously correlating to the air temperature, with positive correlation with the air temperature below 18.7 °C and negative correlation above 18.7 °C. The proposed model is verified using the data collected in 2013 with an accuracy of 91.6%, showing its good ability to forecast the maximum daily power load.